The Value of Character Education: Study of Strengthening Al-Quran Literacy Culture for the Young Generation in the Disruptive Era 5.0 - Dwi Noviani; Nur Khasanah; Achmad Irwan Hamzani; Havis Aravik (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2024)
This research aims to instill the values of character education in strengthening the Al-Quran literacy culture for teenagers at State Vocational Schools in Palembang City. This research uses a pedagogical, historical, and sociological approach where research data comes from primary data and secondary data is obtained from literature or reference books and documents as supporting data. The researchers themselves were the key instruments, and they then developed new instruments, namely observation guidelines, interview guidelines, and documentation. All three are used to collect data in the field. For this research, two main factors play a very important role in strengthening the results of the data analysis study, namely supporting factors and inhibiting factors. The results of this research show that the values of character education in strengthening Al-Qur'an literacy culture implemented at State Vocational Schools in Palembang City are still very low, even though there are 15-minute recitation, tadarrus, and kultum movements held every Friday, but This is caused by the lack of time allocated for implementing Al-Qur'an literacy culture, students are still unable to read the Al-Qur'an and do not have full awareness of implementing the Al-Qur'an literacy culture program, so its implementation is not optimal. The character values instilled in students are religion, honesty, responsibility, discipline, and caring.